Empathic Cognitions Affected by Undetectable Social Chemosignals: An EEG Study on Visually Evoked Empathy for Pain in an Auditory and Chemosensory Context - Hoenen, Matthias; Lübke, Katrin T.; Pause, Bettina M. (Frontiers in Behavioral Neuroscience, 2018)
Reduction of mu activity within the EEG is an indicator of cognitive empathy and can be generated in response to visual depictions of others in pain. The current study tested whether this brain response can be modulated by an auditory and a chemosensory context. Participants observed pictures of painful and non-painful actions while pain associated and neutral exclamations were presented (study 1, N = 30) or while chemosensory stimuli were presented via a constant flow olfactometer (study 2, N = 22). Chemosensory stimuli were sampled on cotton pads while donors participated in a simulated job interview (stress condition) or cycled on a stationary bike (sport condition). Pure cotton was used as a control. The social chemosignals could not be detected as odors. Activity within the 8-13 Hz band at electrodes C3, C4 (mu activity) and electrodes O1, O2 (alpha-activity) was calculated using Fast-Fourier-Transformation. As expected, suppression of power in the 8-13 Hz band was stronger when painful as compared to non-painful actions were observed (study 1, p = .020; study 2, p = .005). In addition, as compared to the neutral auditory and chemosensory context, painful exclamations (study 1, p = .039) and chemosensory stress signals (study 2, p = .014) augmented mu -/alpha suppression also in response to non-painful pictures. . The studies show that processing of social threat-related information is not dominated by visual information. Rather, cognitive appraisal related to empathy can be affected by painful exclamations and subthreshold chemosensory social information.